FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KINERJA PENYULUH PERTANIAN DI KABUPATEN KUTAI KARTANEGARA - Putra, Gisky Andria; Widuri, Nike; Nurfilah, Saripah (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2025)
The decreasing speed and level of utilization of agricultural technology innovations produced by the Agricultural Research and Development Agency (Balitbangtan) raises questions that must be answered through relevant research. Therefore, it is necessary to analyze the factors that support the performance of extension workers based on their personal characteristics and external support. This study is a survey research using a quantitative approach. Data analysis employs the Spearman Rank Correlation technique. The results indicate a significant relationship between respondent characteristics and the performance of agricultural extension workers in Kutai Kartanegara district. The correlation coefficient of 0.469 is interpreted as a positive correlation. This means that the better the personal characteristics of the extension workers (formal education, frequency of training participation, and field of study), the higher their performance. The strength of the relationship between the personal characteristics variable and the performance of agricultural extension workers is categorized as moderate.